2015
DOI: 10.1016/j.reprotox.2014.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Nonclinical reproductive and developmental safety evaluation of the MAGE-A3 Cancer Immunotherapeutic, a therapeutic vaccine for cancer treatment

Abstract: We assessed potential toxic effects of the MAGE-A3 Cancer Immunotherapeutic on female fertility and embryo-fetal, pre- and post-natal development in rats and on male fertility in rats and monkeys. Three groups of 48 female (Study 1) or 22 male (Study 2) CD rats received 5 or 3 injections of 100μL of saline, AS15 immunostimulant, or MAGE-A3 Cancer Immunotherapeutic (MAGE-A3 recombinant protein combined with AS15) at various timepoints pre- or post-mating. Male Cynomolgus monkeys (Study 3) received 8 injections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…This study adds to the developmental and reproductive toxicity data obtained with BioThrax (Conlin et al, 2017; Franco et al, 2009). The current study also shows that the adjuvant CPG 7909 does not produce any reproductive or developmental toxicity in pregnant rats or their offspring, which is consistent with a previous study in rats (Destexhe et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…This study adds to the developmental and reproductive toxicity data obtained with BioThrax (Conlin et al, 2017; Franco et al, 2009). The current study also shows that the adjuvant CPG 7909 does not produce any reproductive or developmental toxicity in pregnant rats or their offspring, which is consistent with a previous study in rats (Destexhe et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…It should be noted that although in a different situation, dosing of rats in a recent combined FD/PPN reproduction toxicology study (with sectioning on day 20 of gestation and littering and observation of offspring until day 25 of age) using a potential therapeutic vaccine (including a immunostimulant adjuvant) for cancer treatment showed an increase in incomplete ossification/unossified of cranial centers from use of the adjuvant (n = 36) among the sectioned fetuses compared to the saline control group (n = 25). 22 The study authors had no specific concern with this finding and reported that there was no indication of reproductive toxicity in this study.…”
Section: Discussionmentioning
confidence: 65%
“…Furthermore, we have also previously assessed the effects of AS15 alone or combined with MAGE‐A3 on fertility and pre‐ and postnatal development in rats and monkeys. Similarly, no signs of systemic toxicity were observed after administration of AS15 or MAGE‐A3 + AS15 in these animals (Destexhe et al ., 2014b). …”
Section: Discussionmentioning
confidence: 99%